Variabilidade genética e teores de metilxantinas e compostos fenólicos em progênies de erva-mate (Ilex paraguariensis St. Hil.) - Friedrich, Juliana Cristhina (2009)
Mate (Ilex paraguariensis St. Hil.), is a plant native to the South America, where it has a great social economic importance. However, the species is threatened by genetic erosion resulting from predatory exploitation, deforestation, and poor seed genetic and physiological quality. Conservation measures should be taken based on the knowledge of the genetic and phytochemical parameters of the species. This work aimed to characterize the genetic and chemical variability between mate progenies collected in Pinhão, Quedas do Iguaçu, Ivaí, and Cascavel, all in Paraná (PR) State, and in Barão de Cotegipe, Rio Grande do Sul (RS) State, using RAPD molecular markers and analysis of methylxantine contents and phenolic compounds by liquid chromatography. The molecular analyses were performed using 20 RAPD primers. The compound quantification data were submitted to variance analysis, mean comparison, and phenotypic, genotypic, and environmental correlation, in addition to Tocher and UPGMA grouping using the generalized Mahalanobis distance ( ) as a reference. The primers used yielded 254 amplified fragments (94.89% polymorphics) and the band size ranged from 300 to 3,533 pb. A larger genetic variability was observed between the progenies (92.00%). The most similar combination occurred between accesses 47 (progeny C 4/4) and 48 (progeny C4/6), for sii' = 0.913, while the combination of accesses 4 (progeny AM 110/1) and 68 (progeny Q 65/6) was the most dissimilar, dii' = 0.718. Compound profiling revealed significant statistical differences in caffeine and theobromine contents between the 16 progenies. The minima and maxima were 0.0129% (progeny BA 25) and 1.3821% (progeny AB 91) for caffeine and 0.01021% (progeny S 69) and 0.8499% (progeny NA 121) for theobromine, respectively. The phenolic acid contents showed differences between progenies only for chlorogenic acid, whose concentration ranged from 1.5924% (progeny AQ 151) to 2.8046% (progeny NA 121). A negative correlation was observed between the concentrations of caffeine and theobromine (-0.8643), and chlorogenic acid (-0.6806), as well as their isomers, neochlorogenic acid (-0.6755) and cryptochlorogenic acid (-0.4264). Theobromine presented a positive correlation with caffeoyl derivatives, 0.4245, 0.7106, and 0.3937 for neochlorogenic, chlorogenic, and cryptochlorogenic acids, respectively. The results evidenced a large genetic and phytochemical divergence between the studied progenies, suggesting that significant gains may be achieved by material selection in species improvement programs.